2010
DOI: 10.1002/pon.1713
|View full text |Cite
|
Sign up to set email alerts
|

Rasch analysis of positive changes following adversity in cancer patients attending community support groups

Abstract: The two domains verified by Rasch analysis can be used through Rasch-transformed measures to make further statistical inference when comparing positive changes following adversity within and between cancer groups. The psychometric properties of the PBS verified by Rasch modeling fit to the unidimensionality, but need a huge sample size to support its validity and reliability in future studies. Nonetheless, we should be cautious to make comparisons among types of cancer patients due to DIF exhibited in scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Ecological theory has successfully predicted that (a) assertive patient behaviors such as making requests, asking questions, and expressing opinions generally promote physicians’ patient-centered behaviors [29,32,34], (b) physicians’ facilitative behaviors such as addressing patients’ concerns and helping patients to participate in care reinforce patient assertiveness [13,35], and (c) when caregivers are present in consultations, they can align the efforts of clinicians and patients towards common communication goals and help patients to understand and use relevant information [36,37]. Ecological theory also partially explains paradoxical results in which some outcomes, such as patient satisfaction and physician frustration, worsen when patients are trained to communicate assertively and physicians are unprepared for change [22,34].…”
Section: Introductionmentioning
confidence: 99%
“…Ecological theory has successfully predicted that (a) assertive patient behaviors such as making requests, asking questions, and expressing opinions generally promote physicians’ patient-centered behaviors [29,32,34], (b) physicians’ facilitative behaviors such as addressing patients’ concerns and helping patients to participate in care reinforce patient assertiveness [13,35], and (c) when caregivers are present in consultations, they can align the efforts of clinicians and patients towards common communication goals and help patients to understand and use relevant information [36,37]. Ecological theory also partially explains paradoxical results in which some outcomes, such as patient satisfaction and physician frustration, worsen when patients are trained to communicate assertively and physicians are unprepared for change [22,34].…”
Section: Introductionmentioning
confidence: 99%
“…2009) have reported that positive social relationships are an important contextual factor for positive thinking and goal attainment. Positive changes following adversity were significantly associated with and ascribed to the duration of patient attendance in community‐based cancer support groups (Chien et al . 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional intervention is usually considered to be a treatment option that helps patients to preserve usual body weight and food intake as well as prevent nutrient deficiencies (Chien et al . ). Although an appropriate assessment method for evaluating the status of malnutrition is vital for comparing patients' malnutrition status (Gavazzi et al .…”
Section: Discussionmentioning
confidence: 97%
“…The malnutrition rate for hospitalised patients in the UK is approximately 40%, and 75% of patients will lose weight after being hospitalised for a week (McWhirter & Pennington 1994). Nutritional intervention is usually considered to be a treatment option that helps patients to preserve usual body weight and food intake as well as prevent nutrient deficiencies (Chien et al 2010b). Although an appropriate assessment method for evaluating the status of malnutrition is vital for comparing patients' malnutrition status (Gavazzi et al 2011;Tu et al 2012) and many nutritional assessment methods, such as SGA (Detsky et al 1987), the MUST (malnutrition universal screening tool) (Stratton et al 2004), and the NRI (nutritional risk index) (Buzby et al 1988;Corish et al 2004), have been most commonly applied to clinical settings, the individual item-by-item (like survey 1 in this study) box plot method has been criticised (Chien et al 2009) because of its measurement errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation